High frequency of submicroscopic chromosomal imbalances in patients with syndromic craniosynostosis detected by a combined approach of microsatellite segregation analysis, multiplex ligation-dependent probe amplification and array-based comparative genome hybridisation. Issue 7 (2nd May 2008) - Jehee, F S; Krepischi-Santos, A C V; Rocha, K M; Cavalcanti, D P; Kim, C A; Bertola, D R; Alonso, L G; D'Angelo, C S; Mazzeu, J F; Froyen, G; Lugtenberg, D; Vianna-Morgante, A M; et al.
Abstract : We present the first comprehensive study, to our knowledge, on genomic chromosomal analysis in syndromic craniosynostosis. In total, 45 patients with craniosynostotic disorders were screened with a variety of methods including conventional karyotype, microsatellite segregation analysis, subtelomeric multiplex ligation-dependent probe amplification) and whole-genome array-based comparative genome hybridisation. Causative abnormalities were present in 42.2% (19/45) of the samples, and 27.8% (10/36) of the patients with normal conventional karyotype carried submicroscopic imbalances. Our results include a wide variety of imbalances and point to novel chromosomal regions associated with craniosynostosis. The high incidence of pure duplications or trisomies suggests that these are important mechanisms in craniosynostosis, particularly in cases involving the metopic suture.